Descripción de los estados financieros correspondiente a las entidades financieras del Ecuador. - Tibanta Castillo, David Ricardo (My University, 2018)
The present case of investigation has the purpose of describing the presentation of the financial information in accordance with the legal norms in force, in conjunction with the local laws allowing the accounting reports that are given within the process have sufficient reasonableness that public banks present , private and popular-solidary, that is why we resort to the application of methodological processes that make known about the studied through search, reading and review of scientific journals that will allow the development and understanding of the process framed in the preparation of the financial statements, significant documents that allow knowing the economic reality of the companies. In this sense, the work is structured initially by the introduction, which corresponds to the literature review of how the applicability of the financial statements arises, in addition to concepts called theoretical framework that encompass definitions framed within the proposed topic, the following part is performed the presentation of the case in question to be resolved, which will proceed to identify the main components that are provided in the financial statements presented in all national financial institutions. Finally, the conclusions that are part of the investigation that relates the applicability, guaranteeing the presentation of the information in an objective and comprehensible way, are provided, in virtue of the fact that the users, whether internal or external, can make the correct decisions efficiently and correctly. within the process of capital investments that are made to the financial economy of the entities.
El presente caso de investigación tiene la finalidad de describir la presentación de la información financiera de acuerdo con las normas legales vigentes, en conjunto con las leyes locales permitiendo que los informes contables que se dan dentro del proceso tengan la suficiente razonabilidad que presentan los bancos públicos, privados y populares-solidarios, es por ello que se recurre a la aplicación de procesos metodológicos que dan a conocer sobre lo estudiado a través de búsqueda, lectura y revisión de revistas científicas que permitirá el desarrollo y comprensión del proceso enmarcado en la elaboración de los estados financieros, documentos significativos que permite conocer la realidad económica de las sociedades. En este sentido, el trabajo se encuentra estructurado inicialmente por la introducción, que corresponde a la revisión bibliográfica de cómo surge la aplicabilidad de los estados contables, además de conceptos denominado marco teórico que abarcan definiciones enmarcados dentro del tema propuesto, la siguiente parte se efectúa la presentación del caso en cuestión a resolver, donde se procederá a identificar los principales componentes que se proporcionan en los estados financieros presentados en todas las instituciones financieras nacional. Inalmente se detallan las conclusiones que forman parte de la investigación que relaciona la aplicabilidad garantizando la presentación de la información de forma objetiva y comprensible, en virtud a que los usuarios ya sean de carácter interno o externos puedan tomar las correctas decisiones de manera eficiente y acertada dentro del proceso de inversiones de capitales que se efectúan a la economía financiera de las entidades.
Keywords: ESTADOS FINANCIEROS; INFORMACIÓN CONTABLE; INSTITUCIONES FINANCIERAS; NORMAS; USUARIOS FINANCIEROS